Typical carcinoid in right middle lobe of pulmonary hypoplasia - Yasuaki Kubouchi; Shunsuke Kojima; Wakako Fujiwara; Tatsuya Miyamoto; Shinji Matsui; Takashi Ohno; Tomohiro Haruki; Hiroshige Nakamura (Surgical Case Reports)
Abstract Background Pulmonary typical carcinoid occurring in hypoplasia of the right middle lobe is very rare. Case presentation A routine examination's chest X-ray revealed an abnormal shadow in the right middle lung field of an 82-year-old Japanese woman. A chest computed tomography scan showed a solid 2.5 × 2.0-cm nodule in the very small right middle lobe. A trans-bronchial lung biopsy of the mass in the right middle lobe was performed; it revealed atypical cells with round nuclei growing in multiple foci, and immunostaining was positive for chromogranin A, synaptophysin and CD56, suggesting pulmonary carcinoid. The preoperative clinical diagnosis of primary lung cancer, cT1cN0M0 stage IA3 was considered. A right middle lobectomy and mediastinal lymph node dissection were performed by video-assisted thoracic surgery. Intraoperatively, the middle lobe of the right lung was very small, with 1- to 2-mm-dia. pulmonary arteries and veins that were considered hypoplastic. The final histopathological diagnosis was typical carcinoid, pT2aN0M0 stage IB based on the presence of pleural invasion. Conclusions Including the present patient, only nine cases of lung cancer occurring within pulmonary hypoplasia have been reported, most of which were typical carcinoid.